Analisa Tingkat Kepuasan Konsumen pada Perumahan Deno Indah Langsa - Afnina Afnina (Mahesa Research Center, 2019)
This study explains the satisfaction felt by consumers as residents of the house in Deno Indah Langsa Housing at a relatively high level of customer satisfaction. It is proven by the dominant level of importance for consumers including clean water supply = 63,077 (ranking 1), Ventilation = 44,103 (ranking 2), Bathroom Facilities = 37,436 (ranking 3), Sunlight = 31,282 (ranking 4), Number of Rooms = 29,231 (rank 5), while achievement satisfaction (calculation of the biggest index results) obtained a proud aspect because most consumers find it easy to get public transportation (79,5) so that it also facilitates schooling (75.9), and makes it easier for consumers to go to the store and to the market (72.3) while the smallest index value is indicated by the number (66.7) which states the ease of going to work. Although there are indicators that have a relatively low ranking, such as lack of recreational facilities (37,436), children's playgrounds (40,513) this needs attention to improve settlement design in the future.